A method for preparing large-size recrystallized silicon carbide sheets using a gypsum board mold for gel casting

Through gel injection molding method, the problem of difficult to prepare large-sized recrystallized silicon carbide sheets using modified silicon carbide powder and carbon fiber composite materials has been solved in the prior art, and high-quality and low-cost product production has been achieved, which has improved the Resistance to bending strength and mechanical properties.

CN118619583BActive Publication Date: 2024-12-24NANTONG SANZER PRECISION CERAMICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411087327.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-24
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

It is difficult to prepare large-size recrystallized silicon carbide sheets with existing dry press molding and grouting molding methods, and there are problems such as high cost and easy to layer crack and warping and deformation of the product.

Method used

By using gel injection molding method, the catalyst is added after vacuum defoaming by mixing monomers, crosslinking agents, deionized water, dispersing agents, defoaming agents, modified silicon carbide powders, carbon fiber composites and sintering aids. and initiator, poured into gypsum board mold to cure and dry, and use modified silicon carbide powder and carbon fiber composite materials to improve the dispersion performance and connection tightness of the product, and reduce cracking.

Benefits of technology

The high-quality large-size recrystallized silicon carbide sheets are prepared, which improves the product's bending strength and mechanical properties, reduces warping and cracking, and reduces production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a method for preparing a large-size recrystallized silicon carbide sheet using a gypsum board mold for gel injection molding, which comprises the following steps: preparing slurry: mixing monomers, crosslinking agents and deionized water, adding dispersants, defoamers, modified silicon carbide powder, carbon fiber composite materials and sintering aids after stirring, adding tetramethylammonium hydroxide after stirring to obtain slurry; preparing green bodies: vacuum degassing the slurry after ball mixing, adding catalysts and initiators to obtain green bodies; green body curing: casting the green bodies in a mold and curing; drying: demolding the solidified green bodies, shaping the green bodies after demolding, then in a constant temperature and humidity drying oven, and then continuously vacuum drying, and finally drying the green bodies in a constant temperature and humidity drying oven to obtain silicon carbide sheet products. The present application has the effect of improving the quality of silicon carbide sheet products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of silicon carbide preparation, and in particular to a method for preparing a large-sized recrystallized silicon carbide sheet using a gypsum board mold for gel injection molding. Background Art

[0002] Recrystallized silicon carbide plates have excellent high temperature resistance, corrosion resistance, hardness, strength, thermal conductivity and other advantages, and are widely used in many fields such as metal processing, furnaces, semiconductors, etc.

[0003] At present, the preparation methods of recrystallized silicon carbide plates produced on a large scale in the market are mainly dry pressing and grouting molding, but both have major defects. Dry pressing has defects such as high cost and inability to prepare large-sized recrystallized silicon carbide plates; grouting molding has problems such as easy delamination and cracking of the product, warping and deformation, and inability to prepare large-sized recrystallized silicon carbide plates.

[0004] Gel casting is a near-net shape molding method that uses a mesh gel generated by in-situ polymerization of organic monomers to fix the ceramic particles in the colloidal system, thereby in-situ molding a ceramic blank with a complex shape. The blank obtained by gel casting is usually strong, and the blank can be finely processed. In addition, the commonly used additives are organic matter, and there will be no impurities left. Therefore, it can produce larger-sized ceramic products, which is in line with the preparation method of recrystallized silicon carbide sheets and has a low cost. However, the recrystallized silicon carbide sheets prepared by this method still have the defect of warping and deformation. Summary of the invention

[0005] In order to improve the product quality of silicon carbide sheets, the present application provides a method for preparing large-sized recrystallized silicon carbide sheets using a gypsum board mold for gel injection molding.

[0006] The present application provides a method for preparing a large-sized recrystallized silicon carbide sheet using a gypsum board mold for gel injection molding, which adopts the following technical solution:

[0007] A method for preparing a large-sized recrystallized silicon carbide sheet using a gypsum board mold for gel casting, comprising the following steps:

[0008] Prepare slurry: mix monomer, crosslinking agent and deionized water, add dispersant, defoamer, modified silicon carbide powder, carbon fiber composite material and sintering aid after stirring, add tetramethylammonium hydroxide after stirring to obtain slurry;

[0009] Preparation of green body: mixing the slurry into balls, vacuum degassing, adding catalyst and initiator to obtain green body;

[0010] Green body solidification: the green body is poured into the mold and solidified;

[0011] Drying: The solidified green body is demoulded, and the green body after demoulding is shaped, and then placed in a constant temperature and humidity drying oven, and then continuously vacuum dried, and finally the green body is dried in a constant temperature and humidity drying oven to obtain a silicon carbide sheet product.

[0012] By adopting the above technical scheme, the silicon carbide powder is modified and then a slurry system is prepared, which can effectively improve the overall dispersion performance of the slurry, reduce the agglomeration of the silicon carbide powder, and make the powder more stable in the slurry, thereby effectively improving the product quality of the prepared silicon carbide plate. Carbon fiber composite materials are also added to the system to promote the tightness of the connection between the components in the system, thereby making the system more stable, and effectively improving the prepared silicon carbide plate to better resist bending stress, and further reducing the cracking phenomenon of the system, further improving product quality.

[0013] Preferably, the mass ratio between the monomer and the cross-linking agent is (7-15):1; the dispersant includes a polymer dispersant, and the dispersant is 1-2.5% of the mass of the modified silicon carbide powder; the catalyst includes tetramethylethylenediamine, and the catalyst is 0.005-0.01% of the mass of the modified silicon carbide powder; the initiator is 5% by mass of ammonium peroxide, and the mass ratio between the catalyst and the initiator is 1:1.

[0014] By adopting the above technical solution and controlling the mass of each component in the system to be within the above range, a more stable silicon carbide sheet product can be obtained.

[0015] Preferably, the modified silicon carbide powder is prepared by the following method:

[0016] Mixing maleic anhydride and sodium hydroxide to obtain a maleic anhydride solution, mixing silicon carbide powder with the maleic anhydride solution, stirring to obtain maleic anhydride treated silicon carbide, adding a silane coupling agent, stirring, centrifuging, washing, and drying to obtain modified silicon carbide powder;

[0017] The silane coupling agent includes any one of KH550, KH560, KH570, KH580, and KH590.

[0018] By adopting the above technical scheme, the silicon carbide ceramic powder is preliminarily treated with maleic anhydride, the silicon carbide powder is coated, and after the negative charge is introduced, it can promote the subsequent addition of the positively charged silane coupling agent, so that the silane coupling agent is enriched on the surface of the silicon carbide powder, and the collision between the silane coupling agent and the silicon carbide surface is improved, thereby improving the grafting efficiency of the coupling agent, so that the silicon carbide powder can be distributed more evenly in the system, thereby improving the product quality.

[0019] Preferably, the carbon fiber composite material includes dopamine composite carbon fiber, epoxy resin and boron nitride components.

[0020] By adopting the above technical scheme, dopamine composite carbon fiber, epoxy resin and boron carbide components are compounded to prepare a carbon fiber composite material, so that the carbon fiber composite material has good interface bonding strength, so that the carbon fiber composite material can be tightly combined in the system, thereby making the system more stable and reducing the occurrence of cracking.

[0021] Preferably, the dopamine composite carbon fiber is prepared by the following method:

[0022] Silver nitrate solution and potassium sulfate are mixed with carbon fiber, washed after ultrasonication, dried, added into Tris buffer, adjusted to alkalinity, dopamine is added, stirred and dried to obtain dopamine-treated carbon fiber, polyethyleneimine is mixed with N,N-dimethylformamide, a dehydration condensation agent is added, refluxed, washed, and dried to obtain dopamine composite carbon fiber.

[0023] By adopting the above technical scheme, flexible polyethyleneimine and rigid dopamine are grafted onto the surface of carbon fiber at one time by chemical grafting, and active groups are introduced. This can make the dopamine composite carbon fiber have a good interface effect, and can better combine with the epoxy resin and slurry system. At the same time, the roughness of the carbon fiber surface is improved, so that the system can better combine with the carbon fiber, promote the uniform propagation of stress, reduce the bending of the prepared plate, and improve the overall mechanical properties of the plate.

[0024] Preferably, the boron nitride component raw materials include boron nitride, glucose and latex.

[0025] Preferably, the boron nitride component is prepared by the following method:

[0026] The boron nitride and glucose are mixed and ball-milled, the mixture is mixed with deionized water, the supernatant is removed after centrifugation, and the boron nitride-glucose complex is obtained after drying. The latex, the boron nitride-glucose complex and deionized water are mixed and stirred, dried, and crushed to obtain the boron carbide component.

[0027] By adopting the above technical solution, the surface of boron nitride is modified by glucose, the C-O bond between the hydroxyl group and carbon of the glucose molecule is broken, and a B-O bond is formed with the polar atom B between the boron nitride, so that the glucose molecule is grafted onto the boron nitride, thereby improving the dispersibility of the boron nitride. After adding latex, the three form a stable cross-linked structure, thereby improving the mechanical properties of the boron nitride component, further improving the overall mechanical properties and uniformity of the product.

[0028] Preferably, the mass ratio of boron nitride, glucose and latex is (0.4-0.5):1:1.5.

[0029] By adopting the above technical solution, preferably the mass ratio of boron nitride, glucose and latex is within the above range, which can further improve the stability of the prepared boron nitride component.

[0030] Preferably, the carbon fiber composite material is prepared by the following method:

[0031] The boron nitride component, dopamine composite carbon fiber and epoxy resin are mixed, and after ultrasonication, they are stirred in an oil bath, a curing agent is added and stirred, and the mixture is dried after exhausting, and then ground to obtain a carbon fiber composite material.

[0032] Preferably, the mass ratio of the epoxy resin, dopamine composite carbon fiber and boron carbide component is 5:1:(0.62-0.68).

[0033] By adopting the above technical solution, the mass ratio between the epoxy resin, dopamine composite carbon fiber and boron carbide component is preferably within the above range, which can further improve the overall stability of the carbon fiber composite material.

[0034] In summary, the present application includes at least one of the following beneficial technical effects:

[0035] 1. The use of modified silicon carbide powder can be dispersed more evenly in the system, thereby improving product quality. At the same time, adding carbon fiber composite materials to the system can make the combination between the components in the system more stable, thereby improving the overall stability of the system.

[0036] 2. After the silicon carbide powder is treated with maleic anhydride, the maleic anhydride is coated on the surface of the silicon carbide powder, and then the powder is modified with a silane coupling agent, which improves the grafting efficiency of the silane coupling agent, thereby improving the interface effect of the silicon carbide powder in the system, and at the same time, the dispersion performance of silicon carbide in the system is improved, further improving the product quality;

[0037] 3. The carbon fiber composite material is prepared by compounding carbon fiber, epoxy resin and boron carbide components with dopamine. After the carbon fiber is modified with dopamine, its interface performance is improved, which can improve the connection performance of each component in the system, promote the propagation of stress, and reduce the bending phenomenon of the board during the preparation process. The boron nitride component is compounded by glucose and latex, so that the overall mechanical properties of the board are improved. A stable three-dimensional network structure is formed between the boron nitride component, dopamine composite fiber and epoxy resin and is evenly distributed in the system, which effectively improves the product quality of the board. DETAILED DESCRIPTION

[0038] The present application is further described in detail below with reference to the embodiments:

[0039] Raw material description: All raw materials in the embodiment can be obtained commercially; wherein, the silicon carbide powder adopts a particle grading, and the mass ratio of the particle sizes of 0.5-1 μm, 40-60 μm, and 100-125 μm is 3.5:3:3.5; the mold for preparing the silicon carbide plate adopts a gypsum board mold, and before the green body is slurried, graphite powder is coated on the inner wall of the mold as a release agent, and the four sides of the gypsum board mold are serrated to reduce cracking, deformation and delamination inside the green body;

[0040] The dehydration condensation agent is N,N-dicyclohexylcarbocyanine (CAS No.: 538-75-0); the monomer is acrylamide (CAS No.: 79-06-1), the cross-linking agent is N,N'-methylenebisacrylamide (CAS No.: 110-26-9), the dispersant is prepared by mixing DolaPIX CE64 dispersant and SOPA (model: DYSP-270) dispersant in a mass ratio of 1:1; the defoaming agent is n-octanol (CAS No.: 111-87-5), and the sintering aid is prepared by mixing carbon and boron carbide in a mass ratio of 1:1; the catalyst is tetramethylethylenediamine (CAS No.: 110-18-9); and the initiator is 5% ammonium persulfate by mass.

[0041] Example 1

[0042] Preparation of modified silicon carbide powder:

[0043] Maleic anhydride (CAS No.: 108-31-6) was mixed with a sodium hydroxide solution, and the pH value was adjusted to 8 to obtain a maleic anhydride solution. Silicon carbide powder was mixed with the maleic anhydride solution, and stirred to obtain maleic anhydride-treated silicon carbide. A silane coupling agent was added, and the mixture was stirred at a speed of 300 r / min for 2 h. After centrifugation, the mixture was washed with deionized water, and transferred to an oven at 75°C for drying for 24 h to obtain modified silicon carbide powder. The mass ratio of maleic anhydride to silane coupling agent was 5:1. The silane coupling agent was KH-550.

[0044] Preparation of dopamine composite carbon fibers:

[0045] The carbon fiber was reflux washed with acetone at 80°C, washed with distilled water, and dried in a vacuum drying oven at 40°C for 8h. 500ml of 0.01mol / L silver nitrate solution and 0.05mol potassium sulfate were mixed with the dried carbon fiber, ultrasonically dissolved, washed with deionized water and ethanol, dried in an oven at 40°C, added to 10mM / L Tris buffer, adjusted the pH value to 8.5 with hydrochloric acid, and then added with dopamine so that the concentration of dopamine (CAS No.: 51-61-6) in the system was 2g / L. After stirring at 25°C, the mixture was dried to obtain dopamine-treated carbon fiber. Polyethyleneimine and N,N-dimethylformamide were mixed in a volume ratio of 1:10, a dehydration condensation agent was added, refluxed at 100°C for 24h, washed alternately with deionized water and ethanol 3 times, and dried at 40°C for 12h to obtain dopamine composite carbon fiber.

[0046] Preparation of Boron Nitride Components:

[0047] 5.51 g of boron nitride was mixed with 13.79 g of anhydrous glucose (CAS No.: 58367-01-4), put into a ball mill, add grinding balls, set the speed of the ball mill to 400 r / min, and ball mill for 16 hours. The ball-milled mixture was mixed with deionized water, centrifuged and the supernatant was removed, centrifuged repeatedly for 3 times, and freeze-dried to obtain a boron nitride-glucose complex. 20.7 g of latex, the boron nitride-glucose complex prepared above, and 300 g of deionized water were mixed, stirred at a speed of 800 r / min for 1.5 hours at 25°C, and crushed to obtain a boron carbide component after drying.

[0048] Preparation of carbon fiber composite materials:

[0049] 28.09 g of boron nitride component, 45.32 g of dopamine composite carbon fiber and 226.59 g of epoxy resin were mixed, and after ultrasonic treatment, they were stirred at a constant temperature of 900 r / min for 3 h in an oil bath at 90°C, 75 g of curing agent D230 was added, and stirred at a speed of 600 r / min for 10 min. The mixture was vented in a vacuum freeze dryer and then dried in a vacuum drying oven at 25°C. After grinding, a carbon fiber composite material was obtained.

[0050] Preparation of large-size recrystallized silicon carbide sheets for gypsum board molds for gel casting:

[0051] Preparation of slurry: 63 g of monomer, 9 g of cross-linking agent and 485 g of deionized water were mixed, and stirred at a speed of 300 r / min for 10 min, followed by adding 12 g of dispersant, 12 g of defoamer, 1200 g of modified silicon carbide powder, 200 g of carbon fiber composite material and 12 g of sintering aid, and stirring at a speed of 800 r / min for 2 h, adding 10 g of tetramethylammonium hydroxide, and stirring at the speed for 2 h to obtain slurry;

[0052] Preparation of green body: Keep the temperature of slurry at 16°C, ball-mill the slurry for 4 hours, vacuum degassing, add 0.1g of catalyst and 0.1g of initiator, and obtain green body after 10 minutes;

[0053] Green body solidification: The green body is poured into the mold and solidified after 30 minutes;

[0054] Drying: demold the solidified body, sandwich the demolded body between two 10mm thick gypsum boards to shape the body, transfer the shaped body to a constant temperature and humidity drying oven (35℃, 50RH) for drying, and after the water immersion rate of the body reaches 3%, continuously vacuum dry it for 3h, and finally place the body back in a constant temperature and humidity drying oven (25RH, 60℃) for drying for 2h, and complete the drying to obtain the silicon carbide sheet product.

[0055] Example 2

[0056] Preparation of modified silicon carbide powder:

[0057] Maleic anhydride and sodium hydroxide are mixed, and the pH value is adjusted to 8 to obtain a maleic anhydride solution, silicon carbide powder is mixed with the maleic anhydride solution, and maleic anhydride treated silicon carbide is obtained after stirring, and a silane coupling agent is continuously added, and the mixture is stirred at a speed of 300 r / min for 2 hours. After centrifugation, the mixture is washed with deionized water, and the mixture is transferred to an oven at 75°C and dried for 24 hours to obtain modified silicon carbide powder; wherein the mass ratio between maleic anhydride and silane coupling agent is 5:1; and the silane coupling agent is KH-560.

[0058] Preparation of dopamine composite carbon fibers:

[0059] The carbon fiber was reflux washed with acetone at 80°C, washed with distilled water, and dried in a vacuum drying oven at 40°C for 8h. 500ml of 0.01mol / L silver nitrate solution and 0.05mol potassium sulfate were mixed with the dried carbon fiber, ultrasonically dissolved, washed with deionized water and ethanol, dried in an oven at 40°C, added to 10mM / L Tris buffer, adjusted the pH value to 8.5 with hydrochloric acid, and then dopamine was added so that the concentration of dopamine in the system was 2g / L. After stirring at 25°C, the mixture was dried to obtain dopamine-treated carbon fiber. Polyethyleneimine and N,N-dimethylformamide were mixed in a volume ratio of 1:10, a dehydration condensation agent was added, refluxed at 100°C for 24h, washed alternately with deionized water and ethanol 3 times, and dried at 40°C for 12h to obtain dopamine composite carbon fiber.

[0060] Preparation of Boron Nitride Components:

[0061] Mix 6.67 g of boron nitride and 13.33 g of anhydrous glucose, put them into a ball mill, add grinding balls, set the speed of the ball mill to 400 r / min, ball mill for 16 hours, mix the ball-milled mixture with deionized water, remove the supernatant after centrifugation, repeat centrifugation 3 times, and obtain a boron nitride-glucose complex after freeze-drying. Mix 20 g of latex, the boron nitride-glucose complex prepared above, and 300 g of deionized water, stir at a speed of 800 r / min for 1.5 hours at 25°C, and after drying, crush to obtain a boron carbide component.

[0062] Preparation of carbon fiber composite materials:

[0063] 28.09 g of boron nitride component, 44.91 g of dopamine composite carbon fiber and 224.55 g of epoxy resin were mixed, and after ultrasonic treatment, they were stirred at a constant temperature of 900 r / min for 3 hours in an oil bath at 90°C, 75 g of curing agent D230 was added, and stirred at a speed of 600 r / min for 10 minutes. The mixture was vented in a vacuum freeze dryer and then dried in a vacuum drying oven at 25°C. After grinding, a carbon fiber composite material was obtained.

[0064] Preparation of large-size recrystallized silicon carbide sheets for gypsum board molds for gel casting:

[0065] Preparation of slurry: 175.5 g of monomer, 11.7 g of cross-linking agent and 520 g of deionized water were mixed, and stirred at a speed of 300 r / min for 10 min, followed by adding 31.2 g of dispersant, 39 g of defoamer, 1560 g of modified silicon carbide powder, 260 g of carbon fiber composite material and 18.72 g of sintering aid, and stirring at a speed of 800 r / min for 2 h, adding 26 g of tetramethylammonium hydroxide, and maintaining the stirring speed for 2 h to obtain slurry;

[0066] Preparation of green body: maintaining the temperature of the slurry at 16°C, ball milling the slurry for 4 hours, vacuum degassing, adding 0.26g of catalyst and 0.26g of initiator, and obtaining the green body after 10 minutes;

[0067] Green body solidification: The green body is poured into the mold and solidified after 30 minutes;

[0068] Drying: demold the solidified body, sandwich the demolded body between two 10mm thick gypsum boards to shape the body, transfer the shaped body to a constant temperature and humidity drying oven (35℃, 50RH) for drying, and after the water immersion rate of the body reaches 3%, continuously vacuum dry it for 3h, and finally place the body back in a constant temperature and humidity drying oven (25RH, 60℃) for drying for 2h, and complete the drying to obtain the silicon carbide sheet product.

[0069] Example 3

[0070] Preparation of modified silicon carbide powder:

[0071] Maleic anhydride and sodium hydroxide are mixed, and the pH value is adjusted to 8 to obtain a maleic anhydride solution, silicon carbide powder is mixed with the maleic anhydride solution, and maleic anhydride treated silicon carbide is obtained after stirring, and a silane coupling agent is continuously added, and the mixture is stirred at a speed of 300 r / min for 2 hours. After centrifugation, the mixture is washed with deionized water, and the mixture is transferred to an oven at 75°C and dried for 24 hours to obtain modified silicon carbide powder; wherein the mass ratio between maleic anhydride and silane coupling agent is 5:1; and the silane coupling agent is KH-570.

[0072] Preparation of dopamine composite carbon fibers:

[0073] The carbon fiber was reflux washed with acetone at 80°C, washed with distilled water, and dried in a vacuum drying oven at 40°C for 8h. 500ml of 0.01mol / L silver nitrate solution and 0.05mol potassium sulfate were mixed with the dried carbon fiber, ultrasonically dissolved, washed with deionized water and ethanol, dried in an oven at 40°C, added to 10mM / L Tris buffer, adjusted the pH value to 8.5 with hydrochloric acid, and then dopamine was added so that the concentration of dopamine in the system was 2g / L. After stirring at 25°C, the mixture was dried to obtain dopamine-treated carbon fiber. Polyethyleneimine and N,N-dimethylformamide were mixed in a volume ratio of 1:10, a dehydration condensation agent was added, refluxed at 100°C for 24h, washed alternately with deionized water and ethanol 3 times, and dried at 40°C for 12h to obtain dopamine composite carbon fiber.

[0074] Preparation of Boron Nitride Components:

[0075] Mix 6.1 g of boron nitride and 13.56 g of anhydrous glucose, put them into a ball mill, add grinding balls, set the speed of the ball mill to 400 r / min, ball mill for 16 hours, mix the ball-milled mixture with deionized water, remove the supernatant after centrifugation, repeat centrifugation 3 times, and obtain a boron nitride-glucose complex after freeze-drying. Mix 20.34 g of latex, the boron nitride-glucose complex prepared above, and 300 g of deionized water, stir at a speed of 800 r / min for 1.5 hours at 25°C, and after drying, crush to obtain a boron carbide component.

[0076] Preparation of carbon fiber composite materials:

[0077] 29.32 g of boron nitride component, 45.11 g of dopamine composite carbon fiber and 225.57 g of epoxy resin were mixed, and after ultrasonic treatment, they were stirred at a constant temperature of 900 r / min for 3 hours in an oil bath at 90°C, 75 g of curing agent D230 was added, and stirred at a speed of 600 r / min for 10 minutes. The mixture was vented in a vacuum freeze dryer and then dried in a vacuum drying oven at 25°C. After grinding, a carbon fiber composite material was obtained.

[0078] Preparation of large-size recrystallized silicon carbide sheets for gypsum board molds for gel casting:

[0079] Preparation of slurry: 113.85 g of monomer, 10.35 g of cross-linking agent and 500 g of deionized water were mixed, and stirred at a speed of 300 r / min for 10 min, followed by adding 20.7 g of dispersant, 24.15 g of defoamer, 1380 g of modified silicon carbide powder, 230 g of carbon fiber composite material and 15.18 g of sintering aid, and stirring at a speed of 800 r / min for 2 h, adding 17.25 g of tetramethylammonium hydroxide, and stirring at the speed for 2 h to obtain slurry;

[0080] Preparation of green body: maintaining the temperature of the slurry at 16°C, ball milling the slurry for 4 hours, vacuum degassing, adding 0.1725 g of catalyst and 0.1725 g of initiator, and obtaining the green body after 10 minutes;

[0081] Green body solidification: The green body is poured into the mold and solidified after 30 minutes;

[0082] Drying: demold the solidified body, sandwich the demolded body between two 10mm thick gypsum boards to shape the body, transfer the shaped body to a constant temperature and humidity drying oven (35℃, 50RH) for drying, and after the water immersion rate of the body reaches 3%, continuously vacuum dry it for 3h, and finally place the body back in a constant temperature and humidity drying oven (25RH, 60℃) for drying for 2h, and complete the drying to obtain the silicon carbide sheet product.

[0083] Example 4

[0084] Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the modified silicon carbide powder, the silane coupling agent used is KH-580.

[0085] Example 5

[0086] Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing the modified silicon carbide powder, the silane coupling agent used is KH5-90.

[0087] Example 6

[0088] Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the boron nitride component, 4.29 g of boron nitride, 14.29 g of glucose and 21.42 g of latex are used.

[0089] Example 7

[0090] Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the boron nitride component, 7.74 g of boron nitride, 12.9 g of glucose and 19.36 g of latex are used.

[0091] Example 8

[0092] Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, when preparing the carbon fiber composite material, the boron nitride component used is 26.03g, the dopamine composite carbon fiber is 45.66g, and the epoxy resin is 228.31g.

[0093] Example 9

[0094] Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the carbon fiber composite material, the boron nitride component used is 32.54g, the dopamine composite fiber is 44.58g, and the epoxy resin is 222.88g.

[0095] Example 10

[0096] Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, glucose is not added when preparing the boron nitride component.

[0097] Embodiment 11

[0098] Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, when preparing the carbon fiber composite material, the carbon fiber is not treated with dopamine.

[0099] Example 12

[0100] Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, when preparing the carbon fiber composite material, the boron nitride composite component is replaced with ordinary boron nitride.

[0101] Embodiment 13

[0102] Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that in Example 13, no epoxy resin is added when preparing the carbon fiber composite material.

[0103] Embodiment 14

[0104] Example 14 is based on Example 3. The difference between Example 14 and Example 3 is that in Example 14, no boron nitride composite component is added when preparing the carbon fiber composite material.

[0105] Embodiment 15

[0106] Example 15 is based on Example 3. The difference between Example 15 and Example 3 is that in Example 15, only silane coupling agent is used to modify the silicon carbide powder.

[0107] Comparative Example 1

[0108] Comparative Example 1 is based on Example 3. In Comparative Example 1, no dopamine-composite carbon fiber is added to the carbon fiber composite material, and only epoxy resin and boron nitride components are included.

[0109] Comparative Example 2

[0110] Comparative Example 2 is based on Example 3, and the carbon fiber composite material of Comparative Example 2 is only ordinary carbon fiber.

[0111] Comparative Example 3

[0112] Comparative Example 3 is based on Example 3, and in Comparative Example 3, the carbon fiber composite material is replaced with an equal amount of boron nitride component.

[0113] Comparative Example 4

[0114] Comparative Example 4 is based on Example 3, and the four sides of the gypsum board mold in Comparative Example 4 are flat.

[0115] Comparative Example 5

[0116] Comparative Example 5 is based on Example 3, and in Comparative Example 5, graphite powder is not coated on the inner wall of the gypsum board mold.

[0117] Comparative Example 6

[0118] Comparative Example 6 is based on Example 3, and the silicon carbide powder is not modified in Comparative Example 6.

[0119] Performance testing

[0120] The samples of Examples 1-14 and Comparative Examples 1-5 were sampled and subjected to the following performance tests:

[0121] (1) Bending resistance test

[0122] The bending strength of the samples was tested according to GB / T 6569-2006 Test method for bending strength of fine ceramics. Each sample was tested three times at room temperature, and the average value was taken. The test results were filled in Table 1.

[0123] (2) Surface performance test

[0124] Observe the surface condition of the product after drying and fill in the test results in Table 1.

[0125] Table 1 Performance test results of silicon carbide plate samples of Examples 1-14 and Comparative Examples 1-5

[0126] Test items Bending strength / MPa Surface phenomenon Example 1 436 The surface is flat, without bending or cracking Example 2 438 The surface is flat, without bending or cracking Example 3 448 The surface is flat, without bending or cracking Example 4 442 The surface is flat, without bending or cracking Example 5 445 The surface is flat, without bending or cracking Example 6 430 The surface flatness decreased, and no bending or cracking occurred. Example 7 431 The surface flatness decreased, and no bending or cracking occurred. Example 8 427 The surface flatness decreased, and no bending or cracking occurred. Example 9 426 The surface flatness decreased, and no bending or cracking occurred. Example 10 432 The surface flatness decreased, and no bending or cracking occurred. Embodiment 11 421 The surface flatness decreased, and no bending or cracking occurred. Example 12 423 The surface is flat, without bending or cracking Embodiment 13 419 Surface flatness decreased, slight bending, no cracking Embodiment 14 417 Surface flatness decreased, slight bending, no cracking Embodiment 15 428 The surface is flat, without bending or cracking Comparative Example 1 412 Surface flatness decreased, slight bending, slight cracking Comparative Example 2 405 Surface flatness decreased, slight bending, slight cracking Comparative Example 3 403 Surface flatness decreased, slight bending, slight cracking Comparative Example 4 419 Surface flatness decreased, slight bending, no cracking Comparative Example 5 422 Surface flatness decreased, slight bending, no cracking Comparative Example 6 418 The surface flatness decreased, and no bending or cracking occurred.

[0127] It can be seen from Table 1 that the bending strength of Examples 1-5 is 426 MPa or above, indicating that the silicon carbide plates prepared in the present application have good bending resistance; the surfaces of Examples 1-5 are all flat and no cracking occurs, indicating that the silicon carbide plates prepared by the preparation method have good product quality.

[0128] In Example 6 and Example 7, when preparing the boron nitride component, the mass ratios of boron nitride, glucose and latex used are not within the range specified in the present application. When the latex content is too much, the sheet isolation effect after the boron nitride and glucose are composited is greater than the constraint and cross-linking effect, and the cross-linking degree of the composite material is difficult to be further improved, making it difficult for boron nitride and glucose to form a sufficient three-dimensional stable structure in the system, affecting the performance of the system; when the latex content is too little, boron carbide agglomerates in the system, affecting the stability of the boron carbide component.

[0129] When preparing carbon fiber composite materials in Examples 8 and 9, the mass ratios of the boron nitride component, dopamine composite carbon fiber and epoxy resin are not within the range specified in the present application. When the content of the boron nitride component is too little or too much, it will affect the bonding effect between it and the dopamine carbon fiber, and the stable rigid-flexible structure between the dopamine composite component and the epoxy resin will be affected.

[0130] In Example 10, glucose was not added when preparing the boron nitride component. The interfacial compatibility of the boron nitride that was not compounded with glucose decreased, and the boron nitride layers were difficult to further separate, resulting in agglomeration. This affected the overall stability of the boron nitride component, and thus affected the performance of the prepared carbon fiber composite material.

[0131] In Example 11, the carbon fiber is not treated with dopamine, the roughness of the carbon fiber surface is difficult to improve, and the interface bonding performance is reduced, the dispersion performance in the system is also affected, and it is difficult to further promote the bonding effect between the components in the system.

[0132] In Example 12, only ordinary boron nitride is used, and the unmodified and uncompounded boron nitride agglomerates in the system, which affects the bonding effect between the dopamine composite carbon fiber and the epoxy resin, making it difficult to form a stable network structure.

[0133] In Example 13, epoxy resin was not added when preparing the carbon fiber composite material. The system without epoxy resin is difficult to combine with the dopamine composite carbon fiber and boron nitride to form a stable structure, which also affects the formation of a stable rigid-flexible structure of the dopamine composite carbon fiber, and the overall performance of the system is reduced.

[0134] In Example 14, no boron nitride composite component is added, which affects the toughness of the multi-carbon fiber composite material and also affects the formation of a stable structure of the carbon fiber composite material.

[0135] In Example 15, only silane coupling agent was used to modify the silicon carbide powder. The electrostatic bonding force of the silicon carbide powder that was not modified with maleic anhydride decreased, making it difficult to graft more silane coupling agent, thereby affecting the dispersion effect of the silicon carbide powder in the system.

[0136] In Comparative Example 1, dopamine composite carbon fiber was not added, and it was difficult for the epoxy resin to form a stable rigid-flexible structure. At the same time, the binding performance of each component in the system was reduced, which affected the quality of the prepared product.

[0137] In Comparative Example 2, the carbon fiber composite material is replaced with ordinary carbon fiber. The surface roughness of the ordinary carbon fiber is difficult to be further improved, and it is difficult to form a stable cross-linked structure and a rigid-flexible structure, and the compatibility between systems is also reduced.

[0138] In Comparative Example 3, the carbon fiber composite component is replaced with a boron carbide component, but it is difficult to further enhance the promoting effect on the mechanical properties of the system.

[0139] In Comparative Example 4, the four sides of the gypsum board mold do not adopt a serrated structure but a flat structure. After the blank is solidified, the stress is difficult to concentrate on the edge, and cracks, deformation and stratification occur inside the blank, affecting the quality of the product and reducing the mechanical properties.

[0140] In Comparative Example 5, graphite powder was not coated on the inner wall of the gypsum template, and the green body was difficult to demould quickly, which affected the subsequent drying effect of the green body and thus affected the product quality.

[0141] In Comparative Example 6, the silicon carbide powder was not modified, so that the silicon carbide powder agglomerated in the system, the uniformity of the system decreased, and the product quality was affected.

[0142] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a large-sized recrystallized silicon carbide sheet using a gypsum board mold for gel casting, characterized in that: The steps include: Preparation of modified silicon carbide powder: maleic anhydride and sodium hydroxide solution are mixed, and the pH value is adjusted to 8 to obtain a maleic anhydride solution, silicon carbide powder is mixed with the maleic anhydride solution, and maleic anhydride treated silicon carbide is obtained after stirring, and a silane coupling agent is added, and the mixture is stirred at a speed of 300 r / min for 2 hours, and the mixture is washed with deionized water after centrifugation, and then transferred to an oven at 75°C and dried for 24 hours to obtain modified silicon carbide powder; wherein the mass ratio between maleic anhydride and silane coupling agent is 5:1; and the silane coupling agent is KH-550; Preparation of dopamine composite carbon fiber: The carbon fiber was refluxed and washed with acetone at 80°C, washed with distilled water, and dried in a vacuum drying oven at 40°C for 8h, 0.01mol / L silver nitrate solution 500ml, 0.05mol potassium sulfate and the dried carbon fiber were mixed, ultrasonically dissolved, washed with deionized water and ethanol, dried in an oven at 40°C, added to 10mM / L Tris buffer, adjusted the pH value to 8.5 with hydrochloric acid, and then dopamine was added to make the concentration of dopamine in the system 2g / L, stirred and dried at 25°C to obtain dopamine-treated carbon fiber, polyethyleneimine and N,N-dimethylformamide were mixed in a volume ratio of 1:10, a dehydration condensation agent was added, refluxed at 100°C for 24h, washed alternately with deionized water and ethanol 3 times, and dried at 40°C for 12h to obtain dopamine composite carbon fiber; Preparation of boron nitride component: 5.51 g of boron nitride and 13.79 g of anhydrous glucose were mixed, put into a ball mill, and grinding balls were added. The speed of the ball mill was set to 400 r / min, and the ball mill was milled for 16 h. The ball-milled mixture was mixed with deionized water, and the supernatant was removed after centrifugation. The mixture was centrifuged repeatedly for 3 times, and the boron nitride-glucose complex was obtained after freeze-drying. 20.7 g of latex, the boron nitride-glucose complex prepared above, and 300 g of deionized water were mixed, and the mixture was stirred at a speed of 800 r / min for 1.5 h at 25 ° C. After drying, the mixture was crushed to obtain a boron carbide component; Preparation of carbon fiber composite material: 28.09 g of boron nitride component, 45.32 g of dopamine composite carbon fiber and 226.59 g of epoxy resin were mixed, and after ultrasonic treatment, they were stirred at a constant temperature of 900 r / min for 3 h in an oil bath at 90°C, 75 g of curing agent D230 was added, and they were stirred at a speed of 600 r / min for 10 min, and the mixture was vented in a vacuum freeze dryer, and then dried in a vacuum drying oven at 25°C, and the carbon fiber composite material was obtained after grinding; Preparation of large-size recrystallized silicon carbide sheets for gypsum board molds for gel casting: Preparation of slurry: 63 g of monomer, 9 g of cross-linking agent and 485 g of deionized water were mixed, and stirred at a speed of 300 r / min for 10 min, followed by adding 12 g of dispersant, 12 g of defoamer, 1200 g of modified silicon carbide powder, 200 g of carbon fiber composite material and 12 g of sintering aid, and stirring at a speed of 800 r / min for 2 h, adding 10 g of tetramethylammonium hydroxide, and stirring at the speed for 2 h to obtain slurry; Preparation of green body: Keep the temperature of slurry at 16°C, ball-mill the slurry for 4 hours, vacuum degassing, add 0.1g of catalyst and 0.1g of initiator, and obtain green body after 10 minutes; Green body solidification: The green body is poured into the mold and solidified after 30 minutes; Drying: demould the solidified green body, sandwich the demoulded green body between two 10mm thick gypsum boards to shape the green body, transfer the shaped green body to a constant temperature and humidity drying oven for drying, and after the water soaking rate of the green body reaches 3%, continuously vacuum dry it for 3 hours, and finally place the green body back in a constant temperature and humidity drying oven for drying for 2 hours, and complete the drying to obtain the silicon carbide sheet product; The mold for preparing the silicon carbide plate is a gypsum board mold. Before the green body is slurried, graphite powder is coated on the inner wall of the mold as a release agent. The four sides of the gypsum board mold are serrated.

2. A method for preparing a large-sized recrystallized silicon carbide sheet using a gypsum board mold for gel casting, characterized in that: The steps include: Preparation of modified silicon carbide powder: maleic anhydride and sodium hydroxide are mixed, and the pH value is adjusted to 8 to obtain a maleic anhydride solution, silicon carbide powder is mixed with the maleic anhydride solution, and maleic anhydride treated silicon carbide is obtained after stirring, and a silane coupling agent is added, and the mixture is stirred at a speed of 300 r / min for 2 hours, and after centrifugation, it is washed with deionized water, and transferred to an oven at 75°C for drying for 24 hours to obtain modified silicon carbide powder; wherein the mass ratio between maleic anhydride and silane coupling agent is 5:1; and the silane coupling agent is KH-560; Preparation of dopamine composite carbon fiber: The carbon fiber was refluxed and washed with acetone at 80°C, washed with distilled water, and dried in a vacuum drying oven at 40°C for 8h, 0.01mol / L silver nitrate solution 500ml, 0.05mol potassium sulfate and the dried carbon fiber were mixed, ultrasonically dissolved, washed with deionized water and ethanol, dried in an oven at 40°C, added to 10mM / L Tris buffer, adjusted the pH value to 8.5 with hydrochloric acid, and then dopamine was added to make the concentration of dopamine in the system 2g / L, stirred and dried at 25°C to obtain dopamine-treated carbon fiber, polyethyleneimine and N,N-dimethylformamide were mixed in a volume ratio of 1:10, a dehydration condensation agent was added, refluxed at 100°C for 24h, washed alternately with deionized water and ethanol 3 times, and dried at 40°C for 12h to obtain dopamine composite carbon fiber; Preparation of boron nitride component: 6.67 g of boron nitride and 13.33 g of anhydrous glucose were mixed, put into a ball mill, and grinding balls were added. The speed of the ball mill was set to 400 r / min, and the ball mill was milled for 16 h. The ball-milled mixture was mixed with deionized water, and the supernatant was removed after centrifugation. The mixture was centrifuged repeatedly for 3 times, and the boron nitride-glucose complex was obtained after freeze-drying. 20 g of latex, the boron nitride-glucose complex prepared above and 300 g of deionized water were mixed, and the mixture was stirred at a speed of 800 r / min for 1.5 h at 25 ° C. After drying, the mixture was crushed to obtain a boron carbide component; Preparation of carbon fiber composite material: 28.09 g of boron nitride component, 44.91 g of dopamine composite carbon fiber and 224.55 g of epoxy resin were mixed, and after ultrasonic treatment, they were stirred at a constant temperature of 900 r / min for 3 h in an oil bath at 90° C., 75 g of curing agent D230 was added, and the mixture was stirred at a speed of 600 r / min for 10 min, and the mixture was exhausted in a vacuum freeze dryer, and then dried in a vacuum drying oven at 25° C., and the carbon fiber composite material was obtained after grinding; Preparation of large-size recrystallized silicon carbide sheets for gypsum board molds for gel casting: Preparation of slurry: 175.5 g of monomer, 11.7 g of cross-linking agent and 520 g of deionized water were mixed, and stirred at a speed of 300 r / min for 10 min, followed by adding 31.2 g of dispersant, 39 g of defoamer, 1560 g of modified silicon carbide powder, 260 g of carbon fiber composite material and 18.72 g of sintering aid, and stirring at a speed of 800 r / min for 2 h, adding 26 g of tetramethylammonium hydroxide, and maintaining the stirring speed for 2 h to obtain slurry; Preparation of green body: maintaining the temperature of the slurry at 16°C, ball milling the slurry for 4 hours, vacuum degassing, adding 0.26g of catalyst and 0.26g of initiator, and obtaining the green body after 10 minutes; Green body solidification: The green body is poured into the mold and solidified after 30 minutes; Drying: demould the solidified green body, sandwich the demoulded green body between two 10mm thick gypsum boards to shape the green body, transfer the shaped green body to a constant temperature and humidity drying oven for drying, and after the water soaking rate of the green body reaches 3%, continuously vacuum dry it for 3 hours, and finally place the green body back in a constant temperature and humidity drying oven for drying for 2 hours, and complete the drying to obtain the silicon carbide sheet product; The mold for preparing silicon carbide plates is a gypsum board mold. Before the green body is slurried, graphite powder is coated on the inner wall of the mold as a release agent. The four sides of the gypsum board mold are serrated.

3. A method for preparing a large-sized recrystallized silicon carbide sheet using a gypsum board mold for gel casting, characterized in that: The steps include: Preparation of modified silicon carbide powder: maleic anhydride and sodium hydroxide are mixed, and the pH value is adjusted to 8 to obtain a maleic anhydride solution, silicon carbide powder is mixed with the maleic anhydride solution, and maleic anhydride treated silicon carbide is obtained after stirring, and a silane coupling agent is added, and the mixture is stirred at a speed of 300 r / min for 2 hours, and the mixture is washed with deionized water after centrifugation, and transferred to an oven at 75°C for drying for 24 hours to obtain modified silicon carbide powder; wherein the mass ratio between maleic anhydride and silane coupling agent is 5:1; and the silane coupling agent is KH-570; Preparation of dopamine composite carbon fiber: The carbon fiber was refluxed and washed with acetone at 80°C, washed with distilled water, and dried in a vacuum drying oven at 40°C for 8h, 0.01mol / L silver nitrate solution 500ml, 0.05mol potassium sulfate and the dried carbon fiber were mixed, ultrasonically dissolved, washed with deionized water and ethanol, dried in an oven at 40°C, added to 10mM / L Tris buffer, adjusted the pH value to 8.5 with hydrochloric acid, and then dopamine was added to make the concentration of dopamine in the system 2g / L, stirred and dried at 25°C to obtain dopamine-treated carbon fiber, polyethyleneimine and N,N-dimethylformamide were mixed in a volume ratio of 1:10, a dehydration condensation agent was added, refluxed at 100°C for 24h, washed alternately with deionized water and ethanol 3 times, and dried at 40°C for 12h to obtain dopamine composite carbon fiber; Preparation of boron nitride component: 6.1 g of boron nitride and 13.56 g of anhydrous glucose were mixed, put into a ball mill, and grinding balls were added. The speed of the ball mill was set to 400 r / min, and the ball mill was milled for 16 h. The ball-milled mixture was mixed with deionized water, and the supernatant was removed after centrifugation. The mixture was centrifuged repeatedly for 3 times, and the boron nitride-glucose complex was obtained after freeze-drying. 20.34 g of latex, the boron nitride-glucose complex prepared above, and 300 g of deionized water were mixed, and the mixture was stirred at a speed of 800 r / min for 1.5 h at 25 ° C. After drying, the mixture was crushed to obtain a boron carbide component; Preparation of carbon fiber composite material: 29.32 g of boron nitride component, 45.11 g of dopamine composite carbon fiber and 225.57 g of epoxy resin were mixed, and after ultrasonic treatment, they were stirred at a constant temperature of 900 r / min for 3 h in an oil bath at 90°C, 75 g of curing agent D230 was added, and the mixture was stirred at a speed of 600 r / min for 10 min, and the mixture was vented in a vacuum freeze dryer, and then dried in a vacuum drying oven at 25°C, and the carbon fiber composite material was obtained after grinding; Preparation of large-size recrystallized silicon carbide sheets for gypsum board molds for gel casting: Preparation of slurry: 113.85 g of monomer, 10.35 g of cross-linking agent and 500 g of deionized water were mixed, and stirred at a speed of 300 r / min for 10 min, followed by adding 20.7 g of dispersant, 24.15 g of defoamer, 1380 g of modified silicon carbide powder, 230 g of carbon fiber composite material and 15.18 g of sintering aid, and stirring at a speed of 800 r / min for 2 h, adding 17.25 g of tetramethylammonium hydroxide, and stirring at the speed for 2 h to obtain slurry; Preparation of green body: maintaining the temperature of the slurry at 16°C, ball milling the slurry for 4 hours, vacuum degassing, adding 0.1725 g of catalyst and 0.1725 g of initiator, and obtaining the green body after 10 minutes; Green body solidification: The green body is poured into the mold and solidified after 30 minutes; Drying: demould the solidified green body, sandwich the demoulded green body between two 10mm thick gypsum boards to shape the green body, transfer the shaped green body to a constant temperature and humidity drying oven for drying, and after the water soaking rate of the green body reaches 3%, continuously vacuum dry it for 3 hours, and finally place the green body back in a constant temperature and humidity drying oven for drying for 2 hours, and complete the drying to obtain the silicon carbide sheet product; The mold for preparing silicon carbide plates is a gypsum board mold. Before the green body is slurried, graphite powder is coated on the inner wall of the mold as a release agent. The four sides of the gypsum board mold are serrated.